Faktor-faktor yang mempengaruhi citra tubuh Pasien diabetes melitus yang mengalami Ulkus diabetikum - Wan Khairul Nizam; Yesi - Hasneli; Arneliwati - - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The purpose of this research is to identify influencing factor of body image among diabetic patient by foot ulcer at Arifin Achmad hospitals Riau province. The research used correlative descriptive with cross sectional approach as its design. The number of samples is 30 people taken using pusposive sampling technique. The analysis used was univariate using frequency distribution and bivariate analysis using chi-square test. Based on the statistical test (chi-square) results, it is concluded that there is significant between changes in body apprearance with body image [p value <α (0,042<0,05)], there is significant between changes in function of body with body image [p value <α (0,011<0,05)], there is significant between reactions of others with body image [p value <α (0,027<0,05)] and there is significant between comparison of others with body image [p value <α (0,033<0,05)]. The result of research expected nurse more pay attention to psychological aspects when giving nursing intervention Keywords: Body Image, Diabetic Ulcers, Influencing Factors of Body Image